Recognition of Prior Learning in Egypt for Citizens and Migrants (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
Egypt’s rapidly growing and youthful population, combined with significant levels of migration and displacement, highlights the urgent need for effective systems to recognize skills acquired outside formal education. This paper examines the current state of Recognition of Prior Learning (RPL) in Egypt for both citizens and migrants, outlining existing practices in the education and labor sectors alongside persistent structural, legal, and institutional gaps. While limited mechanisms—such as literacy certification, leveling exams, and skill measurement tests—provide partial recognition, Egypt lacks a comprehensive national RPL framework aligned with its National Qualifications Framework (NQF). The paper concludes by identifying recent policy developments and proposing evidence-based, coordinated steps toward building an inclusive RPL system that supports labor market integration, regional mobility, and the rights of migrants and refugees.Keywords: Recognition of Prior Learning; Egypt; migrants and refugees; informal learning; labor market integration; National Qualifications Framework; skills recognition; lifelong learning; workforce development